Multiple Sclerosis and Imbalance Visual Interface - Jūratė Penkovskienė; Daiva Imbrasienė; Alvydas Paunksnis; Viktorija Slavinskytė; Rasa Šakalienė; Vilma Juodžbalienė; Lina Malcienė (Lithuanian Sports University, 2020)
Research background. In patients with multiple sclerosis vision disorders affect the balance and gait. Impaired balance, gait increases the risk of collapse. The purpose of this study was to evaluate relationship between visual acuity, balance and gait disorders in people with multiple sclerosis. Research methods. Fullerton balance test, balance confidence scale, up and go test, visual acuity were tested using Snellen methodology with Landolt rings. Research results. Balance of subjects without any visual acuity disorders was significantly better (p < 0.05), gait was also faster in subject without visual acuity disorders, but we did not establish statistical significance (p > 0.05). Conclusions: 1. Balance of subject with multiple sclerosis and decreased visual acuity is impaired, but possibility to fall is low. 2. Balance of subjects with multiple sclerosis and without any visual acuity disorders was significantly better compared to subjects whose had any disorders of visual acuity. Gait in subjects without any visual acuity disorders was faster compared to gait of subjects which decreased visual acuity, but there was no statistical significance established. Keywords: multiple sclerosis, balance, gait, visual acuity disorders.